Quaternary Ammonium Trifluoromethoxide Salts as Stable Sources of Nucleophilic OCF3 - Newton, Josiah J; Jelier, Benson J; Meanwell, Michael; Martin, Rainer E; Britton, Robert; Friesen, Chadron M (Organic letters, 2020)
The reaction of nucleophilic tertiary amines with trifluoromethyl and pentafluoroethyl methyl ethers provides quaternary ammonium trifluoromethoxide (NR4OCF3) and pentafluoroethoxide (NR4OCF2CF3) salts, respectively, in good yields. The new trifluoromethoxide salts disclosed herein are uniquely stable for extended periods of time in both the solid state and in solution, which complements contemporary reagents. Here we describe the preparation of a range of NR4OCF3 salts, their long-term stability, and utility in substitution reactions.